(untitled) (Mongolian Journal of International Affairs, 2020)
Mongolia located between Russia and China has been the object of close attention not only for its geographic neighbors, but also for non-regional states called as “third neighbor”. That’s why Mongolian foreign policy has traditionally been an important part of its development strategy. One of the main roles in the process of determining Mongolia’s foreign policy strategy belongs to the President. Democratic Party candidate Kh. Battulga won at the Presidential elections in 2017. All his steps in the field of foreign policy can be divided into three main areas. Firstly, the President of Mongolia has established himself as a supporter of improving relations with Russia, primarily through intensifying trade and economic cooperation and active personal diplomacy towards the Russian side. Secondly, Kh. Battulga demonstrated diplomacy in the Chinese direction though he had difficult time to build cooperation with the southern neighbor of Mongolia due to his election campaign criticizing China. . . Thirdly, Kh. Battulga made some changes in the strategy of relations with the “third neighbor”. For example, he rejected an active participation in some global international events and stayed indifferent to the idea of “permanent neutrality” of Mongolia. Perhaps the most serious foreign policy initiative of the new President of Mongolia was the idea of joining the Shanghai Cooperation Organization as a permanent member. This idea has caused serious political discussions in the country, dividing the expert network into supporters and opponents of the President’s initiative. However, despite certain changes in Mongolia’s foreign policy under the President Battulga, it is difficult to state a radical turn in the foreign policy strategy. Due to political and legal reasons, as well as the external conditions of social and economic development of Mongolia, the President is not able to change the main foundations and principles of foreign policy of the state formed in the post-socialist period. Meanwhile it could be admitted that in Mongolia’s foreign policy the rationality based on the ideological solidarity (“commonwealth of democracies”) is gradually giving way to the rationality of a geographical contiguity and economic pragmatism.